A gull's story, part 2 : counting at the shore - Finale, Frank, 1942-; Moore, Margie (Bay Head, N.J. : Jersey Shore Publications, 2006)
Little Gull, now too big to be called Baby Gull anymore, flies along the shore counting objects, such as beach umbrellas and sandcrabs, from one to twenty.
Keywords: Gulls -- Fiction; Seashore -- New Jersey -- Fiction; Counting; New Jersey -- Fiction